The commodity currency puzzle - Hilde C. Bjørnland; Håvard Hungnes (Statistics Norway, Research Department, 2005)
This paper addresses the purchasing power parity (PPP) puzzle for commodity currencies. A substantial part of the literature on commodity currencies has found that, despite controlling for the effect of commodity prices, PPP does not hold in the long run. We show that once we also control for the effect of the interest rate differential in the real exchange rate relationship, the discrepancies from PPP are fully accounted for. The analysis is applied to the real exchange rate behaviour in Norway, which has a primary commodity (oil) that constitutes the majority of its exports. We show that with the interest rate differential included in the long run real exchange rate relationship, the real oil price plays a minor role. Adjustment to equilibrium (half-lives) is also substantially reduced, taking no more than one year on average. Hence, contrary to earlier findings on commodity currencies, we have effectively removed the PPP puzzle.
Keywords: C32; F31; 330; Exchange rate; commodity currencies; real oil price; purchasing power parity; uncovered interest parity.